Formation and determinants of inter-municipality commuting in Poland: Network centrality analysis - Tomeczek, Artur F.; Radło, Mariusz-Jan; Szczech-Pietkiewicz, Ewelina (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The article analyses the pattern of regional labour mobility in Poland using inter-municipality commuting data. The research questions concerned directions and factors of labour mobility between cities, to assess the level of the centrality of municipalities and major urban centres within the commuting network in Poland. Methodology: A simple static directed commuting network with 3,094 nodes and 34,986 edges was constructed. Various commonly used centrality measures were calculated: degree centrality, betweenness centrality, closeness centrality, PageRank, HITS (hyperlink-induced topic search), and clustering coefficient. Results: The analysis revealed that all voivodeship capitals have the highest centrality in their respective voivodeships, whereas the PageRank of municipalities depends primarily on the number of large firms. The in-degree of the most influential node (Poland’s capital) is much higher than its out-degree. Hidden centres were identified mostly in suburban areas, associated with the location of large enterprises. It was shown that the determinants of the centrality of cities include population, number of firms, and number of large firms. Implications and recommendations: The analysis of commuting networks has practical applications for regional planning. The network importance of each municipality should be taken into consideration when developing national and regional infrastructure. The study’s approach attempted to holistically capture the commuting network across the country. The research indicates significant interregional differences. Originality/value: The novelty of the research is in the modern network analysis methodology applied to commuting data to quantifiably determine the network centrality of the most important urban areas in Poland.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 56-74
Keywords: commuting network; transportation network; complex network; PageRank; labour mobility; Poland